The political and philosophical writings of William Godwin (Pickering, 1993)
Vol. 1, I: Political writings / ed. by Martin Fitzpatrick. - Vol. 2, II: Political writings / ed. by Mark Philp. - Vol. 3: An enquiry concerning political justice / ed. by Mark Philp. - Vol. 4: An enquiry concerning political justice : variants / ed. by Mark Philp. - Vol. 5: Educational and literary writings / ed. by Pamela Clemit. - Vol. 6: Essays / ed. by Mark Philp. - Vol. 7: Religious writings : with index vol. 1-7 / Mark Philp. 8 parts in 7 vols.